Private Activity in Water and Sewerage Remains Subdued - Perard, Edouard (World Bank, Washington, DC, 2012)
In 2010, 25 water and sewerage projects with private participation reached financial or contractual closure in seven low and middle-income countries, involving investment commitments of US$1.8 billion. In addition, a second partial divestiture of a water utility in China raised US$516 million, bringing total investment commitments for 2010 to US$2.3 billion. That investment remained in the US$2 billion to US$3 billion range of the last six years. However, by number of projects, private activity in 2010 declined by 34 percent compared with 2009, reaching the lowest level in the last 15 years. The lower activity in China accounted for most of this decline. Overall, investment was highly concentrated in a few projects. The three largest projects (one water treatment plant in Mexico, a wastewater treatment plant in Egypt, and a partial divestiture of a water utility in China) accounted for 76 percent of investments.